1994
DOI: 10.1136/vr.134.8.183
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of classical swine fever in Sardinia: a serological survey of wild boar and comparison with African swine fever

Abstract: A serological survey was carried out to establish the distribution of classical swine fever among wild boar in Sardinia, where that disease and African swine fever have been endemic in free-ranging domestic pigs and wild boar living in the mountainous areas of the province of Nuoro for several years. Blood samples were collected from 4752 wild boar shot during the period December 1988 to January 1992. An overall prevalence of 11 per cent was observed and the almost constant rate of about 9.8 per cent detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 0 publications
4
91
1
Order By: Relevance
“…They excrete virus in similar quantities as domestic pigs (see Table 2). However, some authors have suggested that they are less efficient in transmitting the infection to other wild boars than is the case for domestic pigs (Laddomada et al, 1994).…”
Section: Role Of Sus Scrofa In the Epidemiology Of Asfmentioning
confidence: 99%
See 3 more Smart Citations
“…They excrete virus in similar quantities as domestic pigs (see Table 2). However, some authors have suggested that they are less efficient in transmitting the infection to other wild boars than is the case for domestic pigs (Laddomada et al, 1994).…”
Section: Role Of Sus Scrofa In the Epidemiology Of Asfmentioning
confidence: 99%
“…This again highlights the importance of virus heterogeneity, as ASF virus expression in wild boar populations may change over time and will, together with other factors, be influenced by the virulence of circulating strains. In Sardinia and Spain, it has been observed that the virus tends to disappear from wild boar populations if there are no subsequent re-infections through contacts with freeranging infected pigs (Laddomada et al, 1994). Therefore, wild boars are considered not to play a major role as a virus reservoir in the absence of free-ranging, infected domestic pigs (Laddomada et al, 1994;Perez et al, 1998).…”
Section: Role Of Sus Scrofa In the Epidemiology Of Asfmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of Ornithodorus ticks, free-ranging pigs are considered the primary reservoirs of ASFV in Sardinia ± whereas wild boars probably play a secondary role (Firinu and Scarano, 1988;Ruiu et al, 1989;Laddomada et al, 1994a). The rough topography of grazing areas ± where pigs may join different herds, the uncontrolled introduction of pigs from unknown sources, and the feeding to pigs of waste food containing pork were considered major factors in the persistence of ASF in Nuoro (Contini et al, 1982;Wilkinson, 1984).…”
Section: Introductionmentioning
confidence: 99%